Pencapaian Sustainable Development Goals Dalam Penyelenggaraan Pemerintahan Desa - Sasmito Jati Utama; Deasy Arieffiani (Faculty of Social and Political Science, 2025)
Sekapuk Village, located in Ujungpangkah Sub-district, Gresik Regency, has been designated as a model village for the implementation of Sustainable Development Goals (SDGs) among 300 villages in the region. This study aims to describe and analyze the level of SDG achievement, as well as to identify supporting and inhibiting factors in implementing SDG-based village governance. Employing an exploratory qualitative research method, the study focuses on 18 SDG indicators applied in Sekapuk Village. The findings indicate that Sekapuk Village attained an overall SDG achievement score of 71.92. Several indicators showed outstanding results, including clean water and sanitation (91.28), clean and renewable energy (99.72), environmentally responsible consumption and production (91.38), marine ecosystem sustainability (100), and peace, justice, and strong institutions (93.50). The key enabling factors comprise visionary village leadership, availability of natural and developmental resources, and strong community participation. In contrast, major challenges include limited funding, the existence of opposing social groups, and the diminishing sustainability of natural resources, particularly in limestone mining